HARMONISASI DALAM KOMUNIKASI GURU DAN SISWA DI ERA MILENIAL MELALUI BAHASA INDONESIA DAN BAHASA TUBUH YANG BERETIKA - Purnamasari, Hetty; Amrullah, Imron (Universitas Wijaya Kusuma Surabaya, 2020)
Efforts have been made to improve the quality of education and develop the character and culture of the nation, especially by educators. The phenomenon of Indonesian people's lives which shows the weakening of the character and culture of the nation which has been believed to have been a characteristic of the Indonesian Nation. Related to this, the problem of a teacher in guiding and fostering their students is very complex. This happens because of many phenomena, one of which is the rise of global culture and the lifestyle of Pop Culture, life tends to be hedonist. People who do not follow this lifestyle will feel inferior. This phenomenon is considered as the impact of the current of globalization which is no longer possible to stem.Â